Enabling 'just' forms of regeneration in Woodstock, Cape Town - Rolls, Lewin (School of Architecture, Planning and Geomatics, 2017)
The dominance of market-led regeneration has the ability to incapacitate the working class individuals' ability to remain in central inner-city neighbourhoods. The inner-city neighbourhood of Woodstock in Cape Town appears to reflect this problem through private sector development that results in the increase of property prices to the detriment of low-income residents. Research indicates that a large proportion of Woodstock residents cannot afford the resulting increase in cost of living, and resort to living in temporary relocated areas remote from economic opportunities and social amenities. Municipal planners are unable to solve proceeding issues from this type of 'unjust' regeneration, however, it is integral for them to enable more 'just' forms of regeneration which mitigates the impact on lower-income residents. In order to respond to this problem, the present study draws largely from Fainstein's (2010) concept of the 'Just City' which reflect the principles of equity, diversity and democracy. In turn, a theoretical framework was established which assessed the extent to which Woodstock performs as a 'Just City'. The case study and oral history data collection method were used. Research techniques included semistructured in-depth interviews, non-participant-observations, mapping techniques of the current situation, document analysis, and an oral history interview. In addition, informal conversations and personal communication, also played a role in this study. Key findings reveal how Woodstock lacks in a number of requirements to indicate a strong presence of urban justice. Regarding equity; there are minimal affordable housing units and a high demand for social housing. Non-Governmental Organisations take the lead in finding bottom-up strategies to benefit marginalised residents. Furthermore, the Urban Development Zone Tax-incentive does not benefit a wide range of individuals beyond long-time property holders. Regarding diversity; although varied public spaces exist, their 'gated' character reveals an inherent social fragmentation. Despite this, zoning, and land-uses speak towards mixed-used and inclusionary potential. Regarding democracy; residents have representation through activist organisations, yet are still not on an equal footing when it comes to decision-making. In order for planners to enable 'just' forms of regeneration, recommendations are made to create a social housing stock, recast the current urban development tax incentive, and prioritize bottom-up strategies. Further recommendations include the establishment of a 'Woodstock Local Area Overlay Zone', promote Amin's (1999) concept of 'institutional thickness', and to enable community activities through working alongside urban designers.